Embedding of public sector innovation labs - Krogh, Andreas Hagedorn (Politica, 2022)
Public sector innovation labs are becoming an increasingly popular tool for developing new and more meaningful forms of governance in the public sector. Due to weak organizational embedding, however, they rarely generate more than local and transient ideas for new solutions. This article examines how public sector innovation labs become embedded in public bureaucracies. It develops a theoretical perspective on the characteristics of public sector innovation labs, their specific form of value creation, and their inherent “embedment paradox”. Through an explorative case study of three municipal innovation labs, it induces four distinct forms of organizational embedding: plan, process, platform, and person embedment. The article contributes with a novel analytical perspective on the relation between public bureaucracies and public sector innovation labs. It may serve as a point of reference for designers and facilitators of public sector innovation labs aiming to enhance the value of labs through organizational embedding.